2012 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2012
DOI: 10.31438/trf.hh2012.86
|View full text |Cite
|
Sign up to set email alerts
|

Mems-Enabled Retarding Potential Analyzers for Hypersonic in-Flight Plasma Diagnostics

Abstract: We report the design, fabrication, and preliminary characterization of a microfabricated retarding potential analyzer (RPA) that ensures unprecedented grid alignment accuracy. Through refined manufacturing methods, improved tolerances upon assembly serve to increase the signal to noise ratio (SNR). Furthermore, microfabrication permits smaller features overcoming sensor limitations previously barring RPAs from use in very dense plasmas such as those during reentry. Preliminary results show more than a twofold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Improving upon in-plane assembly methods reported by Gassend et al [11], our MEMS RPA extends our previous work [10] by replacing the alumina guide rails and a stainless steel housing with nitride-coated silicon springs. The physical dimensions of our RPA are thus reduced while further refining the sensor's assembly precision by approximately an order of magnitude (conventional machining tolerances are on the order of tens of microns, while Gassend et al demonstrated accuracies of a few microns [11]).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Improving upon in-plane assembly methods reported by Gassend et al [11], our MEMS RPA extends our previous work [10] by replacing the alumina guide rails and a stainless steel housing with nitride-coated silicon springs. The physical dimensions of our RPA are thus reduced while further refining the sensor's assembly precision by approximately an order of magnitude (conventional machining tolerances are on the order of tens of microns, while Gassend et al demonstrated accuracies of a few microns [11]).…”
Section: Introductionmentioning
confidence: 59%
“…The process flow to fabricate the electrodes uses contact lithography, RIE, and DRIE as main processing technologies. The process flow was reported in [10]; however, the electrodes of our fully microfabricated sensors are coated with sputtered gold instead of sputtered tungsten. Integrating the grids and collector to the housing using the deflection springs completes the fabrication of the RPAs.…”
Section: Fabricationmentioning
confidence: 99%
See 3 more Smart Citations